Experimental Parasitism of Synanthropic Flies (Musca domestica, Lucilia sericata, and Sarcophaga heamorrhoidalis) by Parasitoid Wasps (Nasonia vitripennis, Spalangia nigroaenea, and Pachycrepoideus vindemmiae) - Mehdi Khoobdel; Omid Dehghan; Abedin Saghafipour; Ehsan Radi; Javad Rafinejad; Kamran Akbarzadeh; Ahmad Ali Enayati; Hosseinali Lotfalizadeh; Mohammad Moradi; Hossein Sobati (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: One of the most popular methods to control the synanthropic flies is using parasitoid wasps. The aim of this study was to estimate the experimental parasitism rates of pupae of Musca domestica, Lucilia sericata, and Sarcophaga heamorrhoidalis by parasitoid wasps, including Nasonia vitripennis, Spalangia nigroaenea, and Pachycrepoideus vindemmiae. Materials and methods: Pupae of three species of flies, including Musca domestica, Lucilia sericata, and Sarcophaga haemorrhoidalis were exposed to three parasitoid female wasps, including Nasonia vitripennis, Pachycrepoideus vindemmiae, and Spalangia nigroaenea in laboratory condition. The exposure rate was 8 wasps to 10 fly pupae on alternate days up to 5 days. The experiments were performed in triplicate and a total of 2700 fly pupae was exposed to 432 wasps. The parasitism rate and parasitoid host preferences were also determined. Results: Total parasitism of flies was estimated at 22.17%. There was no significant differences in parasitism rate of Musca domestica, Lucilia sericata, and Sarcophaga haemorrhoidalis by Nasonia vitripennis, and Pachycrepoideus vindemmiae, but there was a significant difference in parasitism rate of house fly by the three parasitoids investigated (P<0.01). The Spalangia nigroaenea was active just on pupae of Musca domestica. The highest parasitism rate of the fly species studied was found by parasitized wasps of 5–7 days old. Conclusion: Spalangia nigroaenea can be considered as an efficient and specific parasitoid for biological control of Musca domestica. Other wasp species, including Nasonia vitripennis, and Pachycrepoideus vindemmiae could also be used in integrated fly control programs. Also, in biological control program for flies, 5-7 day parasitoid might be more effective.